Taxonomic and nomenclatural notes on some Andes species (Hemiptera, Fulgoromorpha, Cixiidae) with two synonymies and one homonymy - Haas, Matthé Cornelis De; Cesne, Maxime Le; Bourgoin, Thierry (Zootaxa, 2024)
Two African Cixiidae species names, Andes goniodes and Andes synavei proposed by Emeljanov in 2001 to correct two homonymies published by Synave in 1953, are synonymized respectively with Andes muiri and Andes spinifer, which were already proposed as replacement names by Synave in 1970. Additionally, the name Andes synafenni is proposed as new for the Vietnamese species Andes truncatus Fennah, 1978 preoccupied by the African species Andes truncatus Synave, 1953.